Laboratory Tests for Diagnosis of Chronic Periprosthetic Joint Infection Can Help Predict Outcomes of Two-Stage Exchange. (20th June 2018) - Dwyer, Maureen K.; Damsgaard, Christopher; Wadibia, Jason; Wong, Gordon; Lazar, Damien; Smith, Eric; Talmo, Carl; Bedair, Hany
Abstract : Background: Although 2-stage exchange arthroplasty is the most effective treatment among available strategies for managing chronic periprosthetic joint infection (PJI), rates of its success vary greatly. The purpose of our study was to examine whether objective measurements collected at the time of the diagnosis of PJI could be used to identify patients at risk of failure of 2-stage exchange. Methods: We identified 205 patients across 4 institutions who underwent 2-stage exchange arthroplasty for the treatment of PJI following total hip or total knee arthroplasty. Demographic, surgical, and laboratory data were obtained for each patient from their medical chart. Laboratory values included serum erythrocyte sedimentation rate (ESR), serum C-reactive protein (CRP) level, synovial fluid white blood-cell (WBC) count and neutrophil percentage, synovial fluid and/or tissue culture, and Gram stain. Patients who underwent revision surgery for recurrent infection were considered to have failed the 2-stage procedure. Demographic, surgical, and laboratory variables were compared between the 2 groups. Receiver operating characteristic (ROC) curves were constructed to determine threshold cutoffs for significant laboratory values. Risk ratios and 95% confidence intervals were calculated. Results: Overall, 2-stage exchange was unsuccessful for 27.3% of the patients. Preoperative serum ESR (p = 0.035) and synovial fluid WBC count (p = 0.008) and neutrophil percentage (p = 0.041) were greater in patients with recurrent infection. ROC curve analysis revealed a threshold of >60, 000 cells/μL for synovial fluid WBC count, >92% for synovial fluid WBC neutrophil percentage, and >99 mm/hr for serum ESR. Failure of 2-stage exchange was 2.5 times more likely for patients with an elevated preoperative synovial fluid WBC count, 2.0 times more likely for those with an elevated preoperative synovial fluid WBC neutrophil percentage, and 1.8 times more likely for those with an elevated preoperative serum ESR. Conclusions: Our results demonstrated that a greater number of patients in whom 2-stage exchange arthroplasty ultimately failed had a preoperative synovial fluid WBC count of >60, 000 cells/μL, a synovial fluid WBC neutrophil percentage of >92%, or a serum ESR of >99 mm/hr. Patients with elevated laboratory values had 1.8 to 2.5 times the risk of treatment failure. These data can serve as a clinical guideline to identify patients most at risk for failure of 2-stage exchange. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.